New Age Detection of Viruses: The Nano-Biosensors - Shand, Harshita; Dutta, Swarnab; Rajakumar, Santhosh; James Paulraj, Shalini; Mandal, Amit Kumar; KT, Ramya Devi; Ghorai, Suvankar (Frontiers in Nanotechnology, 2022)
Abstract: Viruses and its related diseases have always posed a significant hazard to humans. The current pandemic caused by the Covid-19 (SARS-CoV-2) virus is the latest illustration of what this tiny organism can do to humanity at large, putting everything at the brink of collapse. So it is reasonable that early diagnosis of infection from viruses remains a crucial step to prevent such human suffering. Many traditional methods are already in use for detecting viruses, including molecular approaches, serological methods, direct virus culture methods, and so on. Such traditional methods though are brilliant at some stages but are not devoid of drawbacks. To overcome the limits of conventional procedures, new techniques have been developed which tried to eradicate the demerits of the former procedures. Biosensors have come up with lot of promises in terms of detecting viruses and diseases connected with them. The development of various types of such biosensors such as Affinity-based nano-biosensors, Nanoisland affinity-based biosensors, Graphene affinity-based biosensors, Nanowires based biosensors, Optical nano biosensors, Fiber optic nano-biosensors, Surface Plasmon Resonance(SPR) based optical nano-biosensors, Total internal reflection fluorescence, Surface-Enhanced Raman Scattering(SERS), Electrochemical nano-biosensors had helped us in rapid and sensitive detection of viruses . Aid to these nanosensors, viral detection now becomes very sensitive, rapid and cost has come down to a significant low. In this review, an attempt has been made to compile all of the different nano-biosensors and thier ways of utilisation. Due attention is given to the fact that the reader get the grasp of the concept with much ease.